MENYAKSIKAN KEKERASAN POLITIK DALAM NOVEL âAZRA JAKARTA - Dardiri, Taufiq Ahmad (Universitas Muhammadiyah Surakarta, 2006)
This article has successfully aroused the violence of humanâs right (HAM) by communists in the era of ironical HAM afterwards. Such a violence happens in the form of political force in the course of stricking, imprisoning, torturing, and kill- ing. Of those motives above, the forces can actually be traced back to its roots, marxis ideology. According to Galtung, it is an ideology as the cause of such vio- lence. He exemplifies with the case that most people have done killing for the sake of ideology. This novel presents an episode significant for the Indonesian historical background, G30S/PKI. The Indonesian Communist Party (PKI) force aimed to internalize its ideology in a country, has a great deal of its victims in the nation. Their violence is far from humanity principles. This case is illustrated by an author by presenting symbolic Moslem characters as the victims of PKI violence.Â Key words: violence, symbolic characters, protagonis, dan konstelasi sejarah.Â